Intrafamilial heterogeneity of congenital optic disc pit maculopathy. (4th May 2017) - Rossi, Settimio; De Rosa, Giuseppe; D'Alterio, Francesco Maria; Orrico, Ada; Banfi, Sandro; Testa, Francesco; Simonelli, Francesca
ABSTRACT: Background : Optic disc pit is a very rare clinical entity. The main complication of this condition is the maculopathy. Report of cases : A 40-year-old Caucasian man and his 6-year-old daughter underwent a complete ophthalmological examination. In both cases ophthalmoscopy examination showed a bilateral white-yellow oval depression in the optic disc. Optical coherence tomography showed maculopathy with different degrees of severity in the two cases. Microperimetry and multifocal-electroretinography showed different degrees of retinal dysfunction in both cases. Molecular genetic analysis was performed and the possible pathogenic role of the MIR204 gene was excluded. Discussion : The findings of our familial cases support the hypothesis that optic disc pit associated with maculopathy could be a genetic disease with an autosomal dominant inheritance pattern. Optical coherence tomography is the most helpful diagnostic tool to assess maculopathy associated with optic disc pit. Microperimetry and multifocal-electroretinography are useful for the diagnosis of macular dysfunction in the early stages, and for the prognosis and follow-up of optic disc pit-maculopathy which is the main cause of visual impairment in these patients. Furthermore, in consideration of the variable expressivity and disease severity reported in our cases, genetic anticipation may be hypothesized.